Smart Bricks Curing System using IoT - S., Elarmathi; C., Purusothaman; N., Prasanth; P., Harishkumar K; A., Mohammed Reyan (Journal of ISMAC, 2024)
The existing curing method for bricks lacks in precision and efficiency, resulting in inferior strength and durability in the finished product. Traditional procedures may result in over- or under-curing, causing cracks and decreased structural integrity. Furthermore, manual monitoring and intervention are labor-intensive and prone to human mistake. A smart bricks curing system designed specifically for concrete bricks is critical for obtaining optimal strength and durability. This technology seeks to reduce cracks that threaten the longevity of concrete by maintaining precise moisture levels during the hydration process. The research’s central feature is the implementation of sensors that continuously monitor moisture and temperature levels within the bricks.
Keywords: Automatic Curing System; Concrete Bricks; Moisture Content; Temperature Monitoring; IoT-based Wireless Networks; Water Management